2016
DOI: 10.1016/j.appet.2015.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Food rejections in children: Cognitive and social/environmental factors involved in food neophobia and picky/fussy eating behavior

Abstract: Food neophobia and picky/fussy eating behavior are presented as the two main forms of children's food rejections which are responsible for a reduction of their dietary repertoire. We review the key factors, presented in the literature, that are involved in food rejections during childhood. We first consider a range of "cognitive factors", such as food perception, mental representations, categorization of food items, and emotions and feelings toward food. Next we focus on "social and environmental factors", as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
112
2
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 213 publications
(127 citation statements)
references
References 166 publications
5
112
2
8
Order By: Relevance
“…Vegetable intake is important in the context of food neophobia, as it concerns mainly fruits and vegetables [31]. Moreover, it is indicated that in general, for children, vegetables are characterized by a lower acceptance level than fruits [32], and is even observed to be the lowest among the acceptance levels for all the food product groups [33].…”
Section: Discussionmentioning
confidence: 99%
“…Vegetable intake is important in the context of food neophobia, as it concerns mainly fruits and vegetables [31]. Moreover, it is indicated that in general, for children, vegetables are characterized by a lower acceptance level than fruits [32], and is even observed to be the lowest among the acceptance levels for all the food product groups [33].…”
Section: Discussionmentioning
confidence: 99%
“…Possible confounders were selected a priori based on the existing literature [1,18,1922]. Information on these variables was obtained from the parental questionnaire completed by the parents at baseline and from The Danish Medical Birth Registry.…”
Section: Methodsmentioning
confidence: 99%
“…Examples for a child who is actively rejecting target foods are ‘you’re learning to like this food’ or ‘maybe you will like it tomorrow’. A positive approach can also include involving children in food-related games, preparation and gardening 17. Meals may have become loaded with negativity, and parents may need ideas for how to get out of this cycle, for example, tea parties or picnics.…”
Section: Parental Experiences Of Feedingmentioning
confidence: 99%